Gratitude Sebagai Prediktor Happiness Pada Anak Terlantar Di LKSA - Afni, Sri Santika (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Happiness is a positive emotion like feelings of pleasure, feeling at ease in life. The aim of this study is to see the contribution of gratitude as a predictor of happiness in neglected children in LKSA. The type of research used is correlational quantitative. The population in this study were 40 people. The type of sampling is simple random sampling, using the slovin formula for an error limit of 5%, samples in this study is 36 people. The data collection technique is to provide a scale of gratitude and a scale of happiness. The reliability of the gratitude scale is = 847, and reliability of the happiness scale is = 883. The data in this study were tested using simple linear regression analysis. The results of this study indicate a contribution of gratitude to happiness, based on the data obtained, the results of simple linear regression analysis with the value of F = 60, 532 (p < 0.01) while the value of R square (R2 = 0.640), t value = 7.780 with a significance value (p < 0.01) and a Beta value (╬▓ = 0.800). it means that gratitude can be used as a predictor of happiness for neglected children in LKSA with a contribution of 64%.Keywords: happiness, neglected children, gratitude